The Effect of Regular and Short-Time Exercise on Serum Lipids and Lipoproteins - Yilmaz, N.; Aktas, M.; Solmaz, M.; Toker, M. (Asian Journal of Chemistry, 2016)
The effects of regular short-time exercise on serum lipids and lipoproteins were investigated. 24 university students (12 males, 12 females) between the ages of 19 and 22 years old were included in this study. Before and after exercise, consisting of basketball training three days a week (60 min per session), total cholesterol (TC), triglyceride (TG), low density lipoprotein-cholesterol (LDL-C), high density lipoprotein-cholesterol (HDL-C) levels were measured in the serum samples. For females, at the beginning and end of the 45 min exercises TC, TG, LDL-C, HDL-C values were measured respectively as 123.12 ± 38.03, 141.82 ± 49.32, 75.00 ± 36.51, 30.20 ± 8.20, 100.78 ± 23.50, 70.70 ± 15.00, 42.21 ± 16.06 and 33.47 ± 9.72 mg/dl. For males, these values were found respectively as 105.68 ± 40.08, 177.05 ± 57.72, 58.13 ± 27.86, 29.50 ± 11.97, 94.06 ± 24.30, 82.05 ± 33.11, 31.82 ± 22.34 and 30.75 ± 15.73 mg/dl. The results showed that there were no significant differences in the pre- and post-exercise between groups for any of the parameters tested, except TG values in female group and LDL-C values in male group. TG levels in girls group and LDL-C levels in boys group had a significant decrease. These results indicate that the regular and short-time exercise has no effect on serum lipid and lipoproteins.